중장년층의 운동참여를 위한 헬스케어 가상현실 콘텐츠 디자인 평가요인 및 중요도 분석 - 전설화(Xue-Hua Quan); 정정호(Jung-Ho Jung) (한국콘텐츠학회 논문지, 24(4), 2024)
본 연구는 중장년층의 운동참여를 위한 헬스케어 가상현실 콘텐츠 디자인의 평가요인들 간의 중요도 차이를 체계적으로 분석하는 데 연구의 목적을 둔다. 이에 본 연구에서는 선행연구를 통해 평가요인들을 도출하고, 가상현실 스크린골프 운동에 참여한 중장년층을 대상으로 평가요인에 대한 설문조사를 진행하였다. 이를 통해 얻은 데이터로 SPSS 통계프로그램을 활용해 탐색적 요인 분석과 신뢰도 분석 및 타당성 검증을 실행하였다. 또한 전문가들의 평가를 바탕으로 AHP 계층분석법을 활용해 각 평가요인들의 중요도를 실증적으로 분석한 뒤, 종합적 가중치를 산출하였다. 그 결과, 상위요인에서는 ‘인지적 요인’이 중요도가 가장 높았으며, 하위요인에서는 ‘균형감’의 중요도가 가장 높은 것으로 확인되었다. 본 연구는 중장년층의 지속적인 운동참여를 위한 헬스케어 가상현실 콘텐츠 디자인에 있어 ‘균형감’이 우선적으로 고려해야 할 요인임을 시사하고, 이를 통해 보다 효과적인 중장년층 운동을 위한 가상현실 콘텐츠를 설계하는 데 참고자료로 제공되기를 기대한다. This study aims to systematically analyze the differences in importance among evaluation factors for the design of healthcare VR content intended to facilitate exercise participation among middle-aged and older adults. To achieve this objective, the study first identifies evaluation factors through a review of existing literature and then conducts a survey among middle-aged and older adults who have participated in VR screen golf exercises. The data obtained from this survey were analyzed using SPSS statistical software to perform exploratory factor analysis, reliability analysis, and validity verification. Furthermore, based on the evaluations by experts, the AHP was utilized to empirically analyze the importance of each evaluation factor and calculate a comprehensive weight. The results revealed that 'Cognitive Factors' were the most important among the higher-level factors, while 'Sense of Balance' was identified as the most critical lower-level factor. This research suggests that 'Sense of Balance' should be a priority consideration in the design of healthcare VR content to support sustained exercise participation among middle-aged and older adults. It is hoped that the findings will serve as a reference for designing more effective VR exercise content for this demographic group. KCI Citation Count: 0